2014
DOI: 10.1007/s10661-014-3925-0
|View full text |Cite
|
Sign up to set email alerts
|

Binary mixtures of diclofenac with paracetamol, ibuprofen, naproxen, and acetylsalicylic acid and these pharmaceuticals in isolated form induce oxidative stress on Hyalella azteca

Abstract: Toxicity in natural ecosystems is usually not due to exposure to a single substance, but is rather the result of exposure to mixtures of toxic substances. Knowing the effects of contaminants as a mixture compared to their effects in isolated form is therefore important. This study aimed to evaluate the oxidative stress induced by binary mixtures of diclofenac with paracetamol, ibuprofen, naproxen, and acetylsalicylic acid and by these nonsteroidal anti-inflammatory drugs (NSAIDs) in isolated form, using Hyalel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 54 publications
(60 reference statements)
2
9
0
2
Order By: Relevance
“…In general, antagonistic interactions increased with the higher concentrations of the mixture. Similarly, Gomez-Olivan et al (2014) found that interactions between two different NSAIDs are fundamentally antagonistic in type.…”
Section: Discussionmentioning
confidence: 95%
“…In general, antagonistic interactions increased with the higher concentrations of the mixture. Similarly, Gomez-Olivan et al (2014) found that interactions between two different NSAIDs are fundamentally antagonistic in type.…”
Section: Discussionmentioning
confidence: 95%
“…Also, it should be considered other contaminants not analyzed in this study. Gómez-Oliván et al (2014b) found values 72 h-LC50 to H. azteca of DCF (4.6 mg L -1 ), IBP (1.7 mg L -1 ), NPX (7.6 mg L -1 ) and PAR (7.7 mg L -1 ) in isolated systems. These results demonstrate that the studied industrial effluent is more harmful to H. azteca than isolated AINEs.…”
Section: Discussionmentioning
confidence: 86%
“…The inhibitory effect on early growth detected on exposure to isolated pharmaceuticals tends to be cancelled in the mixtures, which might be due to interactions between compounds or even to the plant's own metabolism. It is known that the presence of isolated pharmaceuticals in the soil can induce oxidative stress in plants and then, their antioxidant defenses can be induced (Gómez-Oliván et al, 2014), leading to different responses (phytotoxic effects) depending on the pharmaceutical, its concentration and the sensitivity of the plant species (Carvalho et al, 2014;Marsoni et al, 2014;Minden et al, 2017). For instance, IBU acts by inhibiting cyclooxygenases, enzymes that are responsible for the catalysis of the prostaglandins synthesis.…”
Section: Effect Of Pharmaceuticals Mixtures In L Sativa Seedsmentioning
confidence: 99%